Comparing direct and synthetic tests for interruption of line-charging capacitive current. - Daigneault, G.
Using a validated arc model, this paper analyzes current distortion and voltage waveforms during both direct and synthetic tests for interruption of line-charging capacitive current by power circuit breakers. Although the voltage of the electric arc drawn between breaker contacts may produce significant current distortion, it is demonstrated that the most significant parameter affecting the breaking capacity of power circuit breakers in capacitive-current switching tests is the voltage jump appearing across breaker contacts immediately after current interruption. It is essential to correctly define the supply circuit impedances and the associated voltage jump so as not to reduce or increase this test severity unduly
Keywords: Arc model; Breaker contacts; Breaking capacity; Current distortion; Direct tests; Electric arc voltage; Line-charging capacitive current interruption; Power circuit breakers; Supply circuit impedances; Synthetic tests; Voltage jump; Voltage waveforms